Bernyanyi dalam Pembelajaran Bahasa Arab di Yayasan Perguruan Istiqomah Islamic Fullday School - Johar Kurniawan Siagian; Leoni Wilyam; Liana Pratiwi; Haris Atha Hilmi; Sahkholid Nasution (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This thesis discusses how to apply the singing method In learning Arabic, because the majority of Yayasan perguruan Istiqomah Islamic fullday school graduated from elementary school, so that’s not the case Know Arabic. To make it easier for students to learn and To understand Arabic, there needs to bea method used In learning so that learning objectives can be achieved well. Because the success or failureof learning depends on the method used. Especially in learning Arabic, which is language learning Arabicis not easy and sometimes tedious. Internal problem formulation This research is how to apply the deep singing method Arabic language learning at Yayasan perguruan Istiqomah Islamic fullday schoolThis research is a type of field research. Is descriptive qualitative in nature which aims to understand and Describes the application of the singing method in learning Arabic at Yayasan perguruanIstiqomah Islamic fullday school where the researcher Obtain research data by directly visiting Yayasan perguruan Istiqomah Islamic fullday school as a place for research. Researchers use Observation, interviews and documentation methods to explore deep data This research.